2014
DOI: 10.3141/2466-08
|View full text |Cite
|
Sign up to set email alerts
|

Capacity Estimation in Support of Mesoscopic Simulation as Part of Dynamic Traffic Assignment Models

Abstract: Dynamic traffic assignment (DTA) is increasingly being considered to model advanced strategies. Capacity is a crucial parameter in the calibration of traffic flow models utilized as part of DTA modeling. The Highway Capacity Manual has been used as the authoritative source for defining and estimating capacity in the United States. With increased traffic detector data availability in recent years, it is now feasible to locally measure capacity at bottleneck spots with different methods. This study investigates … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…The bilevel strategy increased the share of traffic on local streets, lowering the root mean square error (a common calibration metric) of the model. Shabanian and Hadi used previous data from loop detectors to estimate the capacity at bottleneck locations (16). Their study found the evaluated capacities at some locations to be significantly different from those of the Highway Capacity Manual.…”
Section: Introductionmentioning
confidence: 99%
“…The bilevel strategy increased the share of traffic on local streets, lowering the root mean square error (a common calibration metric) of the model. Shabanian and Hadi used previous data from loop detectors to estimate the capacity at bottleneck locations (16). Their study found the evaluated capacities at some locations to be significantly different from those of the Highway Capacity Manual.…”
Section: Introductionmentioning
confidence: 99%